1991
DOI: 10.1098/rspb.1991.0159
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of tryptophan-21 in mouse nerve growth factor (NGF) affects binding to the fast NGF receptor but not induction of neurites on PC12 cells

Abstract: By using in vitro DNA mutagenesis, we replaced the tryptophan residue at position 21 in mouse nerve growth factor (NGF) with either phenylalanine, leucine or serine. Yield, biological activity, immunological reactivity and receptor binding of the recombinant proteins were determined. All three mutants were produced at considerably lower yields than wild-type NGF, with the serine mutant being undetectable. The results of competitive binding assays show that tryptophan-21 is involved in recognition of the fast N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Having placed biochemical and mutagenesis data for NGF in structural context by analogy with the receptor binding surface of TNF-@, we have shown that the model of NTR fits into the presumptive Color coding of NTR domains is the same as in Figure 2, except that linker residues are not separately colored. binding site on NGF (Rosenberg et al, 1986;Ibaiiez et al, 1990Ibaiiez et al, , 1991Ibaiiez et al, , 1992Ibaiiez et al, , 1993; Drinkwater et al, 1991Drinkwater et al, , 1993 Banner et al, 1993). This complex is formed in a stereospecific way, with docking scores that are more than 75% of the regenerated TNF/TNFR crystal complex.…”
Section: Insights From Molecular Modeling and Dockingmentioning
confidence: 99%
See 3 more Smart Citations
“…Having placed biochemical and mutagenesis data for NGF in structural context by analogy with the receptor binding surface of TNF-@, we have shown that the model of NTR fits into the presumptive Color coding of NTR domains is the same as in Figure 2, except that linker residues are not separately colored. binding site on NGF (Rosenberg et al, 1986;Ibaiiez et al, 1990Ibaiiez et al, , 1991Ibaiiez et al, , 1992Ibaiiez et al, , 1993; Drinkwater et al, 1991Drinkwater et al, , 1993 Banner et al, 1993). This complex is formed in a stereospecific way, with docking scores that are more than 75% of the regenerated TNF/TNFR crystal complex.…”
Section: Insights From Molecular Modeling and Dockingmentioning
confidence: 99%
“…A likely binding site for NTR was identified on NGF using a list of residues generated from binding analyses of NGF derivatives and mutants (Rosenberg et al, 1986;Ibaiiez et al, 1990Ibaiiez et al, , 1992Drinkwater et al, 1991Drinkwater et al, , 1993. Known contact residues were then distributed along a dimer interface of the NGF crystal structure on the assumption that receptors of a family might have similar modes of ligand binding.…”
Section: Analysis Of Receptor-ligand Interactions By Molecular Dockingmentioning
confidence: 99%
See 2 more Smart Citations
“…A derivative, in which 0.9 tryptophans had been oxidized, had only 1.2% the affinity of the native molecule and a derivative with 2 oxindole residues did not compete with native NGF for receptor binding at all. Drinkwater et al (1991) also reexamined this question using site-directed mutagenesis, substituting phenylalanine, leucine, and serine for Trp 21 (W21F, W21L, and W21S). W21S was produced at levels that were below detection, but both W21F and W21L were obtained in sufficient quantities for further testing.…”
Section: Tryptophanmentioning
confidence: 99%